2018
DOI: 10.5114/ada.2018.76227
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tinea versicolor on thiol/disulphide homeostasis

Abstract: IntroductionTinea versicolor is a superficial fungal infection caused by Malassezia spp. Malassezia spp. is a member of the normal human skin flora. It becomes a pathogen by transforming from the yeast form to the mycelium form. The oxidant/antioxidant homeostasis may be responsible for this. Thiol/disulphide homeostasis is a new marker indicating oxidative stress. This homeostasis is affected in many illnesses.AimTo investigate the thiol/disulphide homeostasis in patients with tinea versicolor.Material and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 17 publications
2
13
0
1
Order By: Relevance
“…In many different clinical conditions, TDH was examined to show the severity of oxidative stress and significant results were found [18][19][20][21][22][23]. In our study, it was found that total thiol and native thiol levels were significantly lower in DKA.…”
Section: Discussionmentioning
confidence: 55%
“…In many different clinical conditions, TDH was examined to show the severity of oxidative stress and significant results were found [18][19][20][21][22][23]. In our study, it was found that total thiol and native thiol levels were significantly lower in DKA.…”
Section: Discussionmentioning
confidence: 55%
“…Oxidative stress has been the subject of many studies focussing on various conditions including cutaneous disorders. [4][5][6][7][8][9][10] The dynamic balance of thiol/disulphide, a new indicator of oxidative stress,…”
Section: Discussionmentioning
confidence: 99%
“…21 However, Kilinç et al have failed to reveal significant changes in thiol-disulphide haemostasis in patients with the same condition. 4 Onychomycosis may be associated with several predisposing factors including diabetes, immunosuppression, psoriasis, obesity, advanced age and smoking. [22][23][24] Ateş et al have found higher levels of disulphide, disulphide/native thiol, and disulphide/total thiol, and lower levels of native thiol and total thiol in patients with type 1 diabetes mellitus compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pityriasis versicolor (Pv) juga dikenal sebagai tinea versikolor adalah infeksi jamur superfisial pada kulit yang disebabkan oleh spesies Malassezia spp yang pada keadaan normal merupakan organisme komensal kulit manusia. 1 Pv ditandai oleh makula tidak teratur, plak berbatas tegas, tipis, berupa makula hipopigmentasi, hiperpigmentasi, atau eritematosa pada kulit. 2 Prevalensi Pv di negara tropis, seperti di Indonesia yaitu 50% sampai 60%, sedangkan di negara beriklim dingin seperti Swedia yaitu 0,5% sampai 1,1 %.…”
Section: Pendahuluanunclassified